Antiviral peptides against dengue virus - Lee, Michelle Felicia *; Anasir, Mohd Ishtiaq; Poh, Chit Laa * (Academic Press, 2022)
Dengue virus (DENV) poses a continuous threat to the public health of the global community with over 390 million infections and 25,000 deaths annually. The efficacy of the only licensed dengue vaccine, Dengvaxia, against all four DENV serotypes is less than desirable in real-world setting. In addition, there is a lack of clinically approved antiviral drugs against DENV. This drives an urgent need for the development of novel dengue therapeutics. Technological advancements in recent years have paved the way towards initiating an interest in the development of peptide drugs by the pharmaceutical industry. This chapter highlights the current status of the development of antiviral peptides targeting DENV, strategies that were utilized to design antiviral peptides, interactions that were identified between antiviral peptides and DENV host cell receptors or enzymes, advantages and disadvantages of antiviral peptides, as well as potential ways to overcome their limitations.